ChemInform Abstract: Ynones Merge Activation/Conjugate Addition of Chalcogenoborates ArE‐Bpin (E: Se, S). Issue 10 (February 2016) - Civit, Marc G.; Sanz, Xavier; Vogels, Christopher M.; Bo, Carles; Westcott, Stephen A.; Fernandez, Elena
Abstract: The pull‐push effect of the Bpin moiety is applied in the addition of substrates (II) and (IV) to ynones (I) favouring the Z isomers of resulting β‐sulfanyl/selenyl‐enones.